Towards Paravirtualized Network File Systems - Legtchenko, Sergey; Rowstron, Ant (6th USENIX Workshop on Hot Topics in Storage and File Systems (HotStorage 14), 2014)
The virtualized storage stack used in enterprise data centers provides two mechanisms to enable virtualized applications to store and retrieve data, namely, virtual disks and network file systems. In this paper, we examine the pros and cons of using these two mechanisms to integrate emerging non-volatile memory devices, and show how neither of them provide low-overhead access to data without sacrificing compatibility with other popular virtualization-enabled features. In doing so, we present paravirtualized NFS, an alternate mechanism for accessing data, highlight its benefits, and outline research challenges involved in realizing it in practice.